Temporal Drag : Pauline Boudry/Renate Lorenz. - Musée cantonal des Beaux-Arts, Lausanne (Ostfildern : Hatje Cantz, 2011)
With essays by Freeman, Elizabeth; Danbolt, Mathias; Diederichsen, Diedrich; Siegel, Marc; Pernet, Denis and a conversation with the artists by Thal, Andrea
Published on the occasion of two exhibitions: "Accrochage [Vaud 2011]" at the Musée cantonal des Beaux-Arts, Lausanne, 21.01.2011 - 20..02.2011 and "Contagieux! rapports contre la normalité" at the Centre d'art contemporain Genève, which was curated by Denis Pernet, 10.06.2010 - 15.08.2010.
boek
Keywords: Boudry, Pauline; Lorenz, Renate